Methodology of Evaluating the Attractiveness of Wine Tourism Facilities in the Transcarpathian Region of Ukraine - Миронов Юрій Богданович; Kudla Nazar (My University, 2020)
Wine tourism is an important element of two industries – viticulture and tourism. For the tourism industry, wine is a significant factor of the tour attractiveness, a motive for a special trip. The goals and methods of wine tourism fully correspond to the social and humanitarian mission of tourism as an important factor in the dialogue of cultures, respect for universal cultural values, and tolerance towards the way of life, worldview and traditions of other peoples. Materials and methods. The paper uses a point method for evaluating certain parameters of wine tourism facility attractiveness. According to the defined list, the marketing research with a survey of 22 participants of the Chervene Vyno Festival was conducted in Mukachevo (Ukraine) in 2020 and sources of information regarding three wineries were analysed. Results. The evaluation of wine tourism facilities under examination took into account three components of attractiveness: tourist resources, infrastructure and communication accessibility. The methodological basis of the research consists of ten criteria that were evaluated on a scale from 1 to 5 points. The defined criteria form the discussion basis for the needs of improving and modifying the evaluation procedure. Conclusions. The proposed methodology allows evaluating wine tourism facility attractiveness and identifying the leaders of this market. The results of this study can be verified by conducting marketing surveys of tourists and standardized reports with winemakers. Beyond subjectivism in determining the evaluation criteria, the obtained results show the actual offer condition and the adaptation of wine tourism facilities to the service of tourists.
Keywords: tourism; attractiveness; wine tourism facilities; wine